Unbecoming - Downham, Jenny (New York Scholastic Inc., 2016)
Life has just become very complicated for seventeen-year-old Katie; her father walked out a year ago, her mother is stressed out, her brother is a "special needs" teenager, and she is caring for the maternal grandmother she has never met, who is suffering from Alzheimer's--and Katie has a secret of her own that she cannot reveal.
"First published in the United Kingdom in 2015 by David Fickling Books"--Copyright page.
Keywords: Families; Alzheimer's disease -- Patients; Family secrets; Mothers and daughters; Brothers and sisters; Grandmothers; Family life; Alzheimer's disease; Secrets; Alzheimer's disease -- Patients; England; Fiction; Juvenile works